Total addiction : The life of an eclipse chaser - Russo, Kate (Springer Berlin Heidelberg, 2012)
Seeing a total solar eclipse is often described as a once-in-a-lifetime experience. However, for many who have experienced totality, once-in-a-lifetime is simply not enough. They want more, and are willing to go to great lengths often at great expense to repeat the experience. What is it like to experience totality? What is it about the experience that motivates these eclipse chasers? Is there an eclipse chaser personality? Can eclipse chasing actually be described as an addiction? This book describes the people who dedicate their lives to chasing their dream.